THE RELATIONSHIP BETWEEN SUPERVISORS’ ROLE AND QUALITY DELIVERY OF EDUCATION IN GHANAIAN BASIC SCHOOLS - danquah, Mustapha bin; Baidoo, Usman Yaw; Dankwah, Musah; Acheampong, Richmond (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The main focus of the study was to investigate the relationship between the supervisor’s role and qualitative delivery of education at the basic levels in Ghana. Qualitative research paradigm was adopted for the study. Research instruments comprised observation and in-depth interview of participants with the objective of examining the roles and responsibilities of supervisors and its implication for quality education. Schools and participants for the study were selected via purposive sampling. With the aid of the sampling approach, five public primary schools in Assin South Municipality were selected and 50 teachers with 10 headteachers and their assistants were selected for the study. In all, 60 participants responded to the questionnaire in line with the objectives of the study. Findings revealed that supervisors are saddled with the responsibility of upgrading teachers’ professional qualification through practical counseling and sharing of vital information regarding teaching and learning, improving the level of teachers confidence, provide regular progressive report on educational activities of schools under their supervision to the headquarters so as to keep them up-to-date on school needs and success. More importantly, the result of the study revealed that supervisors’ role is positively related and sine-qua-non to qualitative delivery of education in terms of teachers’ professional development and students’ achievement academically. It is therefore recommended that supervisors should be provided regular and effective in-service training so as to augment their supervisory skills. Moreover, efforts should be made by the supervisor to prioritize supervision of instruction over managerial duties since at the long run supervision hold several benefits in connection with the overall objective of educational institutions especially at the basic level